STUDENTS’ PERCEPTION ON THE USE OF RUANGGURU APPLICATION IN THEIR ENGLISH LEARNING - Fatimannisa, Aulia; Dollah, Syarifuddin; Abduh, Amirullah (Interference: Journal of Language, Literature, and Linguistics, 2020)
Abstract. This study aimed at finding out the Students’ Perception on the Use of Ruangguru Application in Their English Learning. The researcher applied mixed method (quantitative and qualitative). The population of this research was the second grade students of Senior High School of Athirah Islamic School Makassar in 2019/2020 academic year. The sample was taken consisted of 24 students which were taken by using simple random sampling technique. The data were obtained through the questionnaire were analysed and tabulated based on the classification of perception using Likert scale and the data from interview were analysed by recording and transcribing it. The results of data analysis showed that (1) students’ perception was positive on the use of Ruangguru application in their English learning by mean score 70 (2) based on the students’ classification that 5 (20.8%) students classified as Strongly positive, 10 (41.7%) students classified as Positive, 5 (20.8%) students classified as Moderate, 3 (12.5%) students classified as Negative and 1 (4.5%) students classified as Strongly negative. This was indicated that most students like using Ruangguru in their English learning.